A study of site response in the Longmen Shan and adjacent regions and site response models for the Sichuan Basin - Guo, Zhen; Chapman, Martin (Frontiers in Earth Science, 2023)
We investigated the regional attenuation and site responses in the Sichuan Basin and adjacent Songpan-Ganze terrane of the Tibetan Plateau using seismic data recorded at 41 stations from regional earthquakes occurring between January 2009 and October 2020. Fourier amplitude spectra of Lg waves were computed and binned into 18 frequency bins with center frequencies ranging from 0.1 Hz-20.4 Hz. The quality factor is estimated as Q(f)=313f^0.74 for the Sichuan Basin and Q(f)=568f^0.34 for the Songpan-Ganze terrane, reflecting significant differences in the crustal structure beneath these two regions. Relative to the Songpan-Ganze terrane, site responses in the Sichuan Basin are characterized by strong amplification effects at frequencies lower than 6 Hz and obvious attenuation at higher frequencies (> 10 Hz). κ_0 of stations in the Sichuan Basin show clearly geographical dependence with an average value of 0.045 s, whereas stations in the Songpan-Ganze terrane generally have smaller κ_0 values with an average value of 0.028 s. In particular, site response and κ_0 of stations in the Sichuan Basin are found to be dependent on the geographically variable thickness of the sedimentary deposits (sediment thickness). These units are comprised of sedimentary rock and semi-consolidated sediments, with a maximum thickness reaching approximately 10 km. Site response terms in the Sichuan Basin derived from the Lg Fourier spectra exhibit consistent patterns versus sediment thickness as frequency increases. We developed site response models as functions of sediment thickness for stations in the Sichuan Basin. The site response model derived from Lg site terms is consistent with that based on site response terms from coda amplitude spectra and horizontal to vertical (H/V) spectral ratios. The models were then incorporated in the stochastic method of ground motion predictions in the Sichuan Basin for six earthquakes occurring between October 2020 and June 2022. Residual analysis suggests that incorporating the site response models as functions of sediment thickness can improve the ground motion prediction model for the Sichuan Basin from moderate earthquakes.